The duties of the almoner (memorandum) - Mudd, Edith E.
1901-10-25 1901 1900s 5 pages To the Governors of St. George's Hospital. Gentlemen: I have received an intimation that Members of the Board are about to consider the duties of the Almoner and I am led to believe that in their opinion the work of that officer has hitherto partaken too much of the nature of relief work. In face of this knowledge I beg to submit the following considerations to your notice, based only on the fact that the Foundation of the Almoner's office was to limit the attendance of Out Patients to those who after enquiry were consider eligible. The general acceptation of the term "Out Patient Abuse" is apparently a very limited one - i.e., implying the attendance at Hospitals of those who are able to pay for their advice and medicine. I am convinced that a short time spent in an Out Patient Department of any Hospital would quickly lead to a wider acceptation of the term. Out Patient abuse might roughly be classed under Three heads:- Class I. In the sense of ineligibility above referred to Class II. In negligence on the part of Patients to carry out the course of treatment prescribed, resulting in: (a) Consequent failure of cure or delay in effecting the same. (b) Lack of satisfaction to the Physician or Surgeon in 378/IMSW/A/1/4/3a